Study on incidence of oesophageal carcinoma in patients undergoing upper gastrointestinal endoscopy for upper gastrointestinal symptoms in a secondary care hospital - Puttaraju, Shashidhara; Gnanakumar, Deva Keerthana Yesudian (International Surgery Journal, 2019)
Background: Oesophageal carcinoma is one of the leading causes of cancer related deaths worldwide and is also associated with high morbidity. Hence early diagnosis and treatment are the only effective way to improve survival and quality of life in oesophageal carcinoma patients. Early-stage oesophageal carcinoma are often asymptomatic and may also present with common upper gastrointestinal symptoms hence diagnosis of early oesophageal carcinoma is only based on detection of suspicious lesions through endoscopy and histopathological evaluation of biopsies from these suspicious lesions. The study is designed to see whether using alarming upper gastrointestinal symptoms, risk of oesophageal carcinoma in patients can be predicted. Methods: Present study comprises of 200 patients presenting with upper gastrointestinal symptoms at JSS Hospital, Chamarajanagar (both out patients and referred patients) during the period of October 2018 to December 2019, who underwent upper gastrointestinal endoscopy. Results: Out of 200 patients, 135 patients were males and 65 patients were females. According to the study, dysphagia was found to be a significant predictive factor and in contrary to the global statistics this study showed females aged more than 60 years were significantly at higher risk of developing oesophageal carcinoma. Conclusions: We recommend to do an early endoscopy for any patient presenting with upper gastrointestinal symptoms and to take multiple biopsies from any suspicious lesion especially for male gender older than 50 years and female gender older than 60 years presenting with dysphagia.